2016
DOI: 10.1039/c5ra18836a
|View full text |Cite
|
Sign up to set email alerts
|

Development of direct gas injection system for atmospheric-pressure in-solution discharge plasma for plasma degradation and material syntheses

Abstract: By applying a high pulsed voltage to a gap between two electrodes placed in a solution, an atmosphericpressure in-solution glow (ASG) plasma is generated. The ASG plasma is applied in a new material processing method, called solution plasma processing (SPP). In order to accelerate the reaction and to add functions to the synthesized materials, it is important to alter the gas content in the ASG plasma. We developed a direct gas injection system for an ASG discharge cell. When O 2 , CO 2 , N 2 and Ar gases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In general, the electron temperature is higher than the ion temperature in the case of non-equilibrium plasma25. However, the temperature at the center of the plasma is still high, i.e., approximately 4000 K2627, even though the solution temperature is maintained at approximately room temperature. Thus, a temperature gradient exists between the center of the plasma and the plasma–solution interface.…”
mentioning
confidence: 97%
“…In general, the electron temperature is higher than the ion temperature in the case of non-equilibrium plasma25. However, the temperature at the center of the plasma is still high, i.e., approximately 4000 K2627, even though the solution temperature is maintained at approximately room temperature. Thus, a temperature gradient exists between the center of the plasma and the plasma–solution interface.…”
mentioning
confidence: 97%
“…The result showed that the high concentration of dissolved O 2 insignificantly increases the amount of H 2 O 2 . Moreover, Yui et al developed a direct gas injection system at the tip of the electrode, as shown in Figure 7 b [ 5 , 65 ]. The injecting gases were O 2 , CO 2 , N 2 , and Ar.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%
“… Systems with different configurations of adding bubbles, proposed by ( a ) Goto et al [ 51 ] and ( b ) Yui et al [ 65 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 We have also succeeded in arranging the gas composition in the ASG plasma by developing a direct gas introducing system through pipe electrodes. 12 The ASG plasma exhibits another characteristic discharge mode. When the distance between the electrodes is extended to more than several millimeters, the ASG plasma, spatially connecting both edge of the electrodes, is separated into two plasmas, localized at the vicinities of the anodic and cathodic electrodes.…”
Section: Introductionmentioning
confidence: 99%